2020
DOI: 10.1002/ange.202000048
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional AuI‐based AIEgens: Manipulating Molecular Structures and Boosting Specific Cancer Cell Imaging and Theranostics

Abstract: Gold(I) N-heterocyclic carbene (Au I -NHC) complexes have emerged as potential anticancer agents owing to their high cytotoxicity and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 60 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…We were inspired by previous examples of NHC-Au I complexes used in cell imaging and anticancer applications. [68][69][70][71][72][73] Considering that the fluorescence behavior and stability of MIC-Au I complex and organometallic cages [M 4 (2) 2 ](OTf) 4 (M = Ag and Au) are significantly improved, we report the first confocal laser scanning microscopy (CLSM) studies of organometallic cages [M 4 (2) 2 ](OTf) 4 (M = Ag and Au) clearly demonstrating cell imaging ability. These studies used three different cancer cell lines representing different types of cancer: A549 (nonsmall cell lung cancer), HeLa (cervical cancer), and SMMC-7721 (hepatocellular cancer).…”
Section: Mechanochromic Propertiesmentioning
confidence: 99%
“…We were inspired by previous examples of NHC-Au I complexes used in cell imaging and anticancer applications. [68][69][70][71][72][73] Considering that the fluorescence behavior and stability of MIC-Au I complex and organometallic cages [M 4 (2) 2 ](OTf) 4 (M = Ag and Au) are significantly improved, we report the first confocal laser scanning microscopy (CLSM) studies of organometallic cages [M 4 (2) 2 ](OTf) 4 (M = Ag and Au) clearly demonstrating cell imaging ability. These studies used three different cancer cell lines representing different types of cancer: A549 (nonsmall cell lung cancer), HeLa (cervical cancer), and SMMC-7721 (hepatocellular cancer).…”
Section: Mechanochromic Propertiesmentioning
confidence: 99%
“…The sensitization enhancement ratio (SER, calculated by SER = D q (Control group)/D q (Treated group)) [ 54 , 55 ] of Au 4 -IO NP-cRGD for 4T1 cells was calculated to be 1.573 (Fig. 3 b), which was slightly higher than that of the commonly used Au drug auranofin (1.462) [ 35 ]. In addition, the SER of Au 4 -IO NP for 4T1 cells was calculated to be 1.436 (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Above mentioned results demonstrated that the as-prepared Au 4 -IO NP-cRGD could induce abundant •OH production, serious DNA damage and effective caspase 3/7 activation under X-ray irradiation, resulting in enhanced therapeutic efficiency of Au 4 -IO NP-cRGD based RT. Additionally, previouly reported Au NCs affected thioredoxin reductase (TrxR) activity could also be a possible mechanism for the synergetic treatment effect [ 35 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…[12] It is precisely the combination of the luminescence properties of Au-NHC complexes, together with their potential therapeutic properties, what makes this type of compounds especially useful in the development of optical theranostic agents. [13][14] Gold (I) complexes are known to form linear compounds with aryl-acetylides. [15] This structural property has been extensively used for the preparation of oligomeric and polymeric materials with attractive photophysical properties.…”
Section: Introductionmentioning
confidence: 99%